Our Experience of Nutraceutical Effects in Age-Related Macular Degeneration - S. V. Yanchenko; A. V. Malyshev; S. N. Sakhnov; A. S. Balayan; A. A. Sergienko (Oftalʹmologiâ, 2020)
Purpose: to assess the possibilities of ophthalmonutraceuticals using in age-related macular degeneration (AND) patients.Patients Methods. The study included 35 patients (68.3 ± 6.3 years old; 15 men, 20 women) with AMD (AREDS-2 and AREDS-3 categories). As an ophthalmic nutraceutical, a biological active supplement was used, included vitamins C and E, zinc, lutein, zeaxantine, cooper, selenium (Retinorm; 3 capsules per day with meals). The observation period was 12 months (6 courses of therapy). There were the main control points: examination at study entry and examination at study completion. All those observed patients were underwent standard ophthalmological examination; fundus state photo registration (Nidek); OCT (Opto-Vue). The significance of a possible increase in the proportion of AREDS-3–4 AMD category patients was assessed using the Pearson γ2 test. An additional criterion was the maximum corrected visual acuity (MCVA) stabilization. The mean and its standard deviation (M ± s) were calculated, the significance of differences was assessed using the Wilcoxon’s t-test.Results. The study was completed in 33 patients. In 2 eyes a transition of AMD from the AREDS-2 to AREDS-3 category was recorded (an increase in the number and size of druses, with the appearance of large druses). The increase in the proportion of patients with the AREDS-3 AMD category was statistically insignificant (γ2 = 0.267; p = 0.606). In no case was there a transition to the AREDS-4 category. In the vast majority of those who completed the study (31 eyes; 93.9 %), the manifestations of AMD were stable, which, taking in account the chosen criterion, allows us to consider nutraceutical support to be affective. MCVA during the observation period also remained stable with a slight, but statistically insignificant tendency to its increase (from 0.72 ± 0.07 to 0.75 ± 0.09; t = 37.5, p > 0.05). One patient was excluded from the study after 6 months of observation due to development of an allergic skin reaction (presumably to the components of a nutraceutical). In the vast majority of patients (97.1%), no significant side effects of therapy were observed, the nutraceutical regimen was comfortable. One more patient was excluded from the study (after 3 months) due to his failure to appear for next follow-up examination.Conclusion. The use of Retinorm ophthalmonutraceutical can stabilize the manifestations of AMD (AREDS-2–3) in 93.9 % of patients with follow-up periods of up to 12 months. Repeated courses of therapy in 97.1 % of patients are not accompanied by significant side effects, and the regimen for taking ophthalmonutraceuticals is characterized by patients as comfortable.